The effect of zoledronic acid on BSP expression and methylation during osteoblastic differentiation of mesenchymal stem cells - M Farsh Dusty Hagh (پیاورد سلامت, 2011)
Background and Aim: Bone sialoprotein (BSP) is a specific marker of osteoblastic differentiation. In this research, the effect of Zoledronic Acid on BSP expression and methylation status during osteoblastic differentiation of mesenchymal stem cells (MSCs) was evaluated. Materials and Methods: In this experimental study, MSCs were isolated from human bone marrow. For osteogenic differentiation, hMSCs were pulse treated with zoledronic acid, and were incubated in osteogenic differentiation medium for 3 weeks. The DNA and RNA were extracted after the first, second and third weeks of culture and also from undifferentiated MSCs. After Sodium bisulfate (SBS) treatment, gene specific methylation analysis for BSP was carried out using Methylation Specific PCR technique. Results: BSP expression was observed in osteoblastic differentiated cells whereas it was not seen in MSCs. MSP showed that BSP was unmethylated during osteoblastic differentiation. Conclusion: BSP was expressed from the first week of differentiation. This confirms that zoledronic acid accelerates osteoblastic differentiation. Unmethylation status of BSP indicates that zoledronic acid does not have any effect on BSP methylation status. Other genetic or epigenetic mechanisms may control BSP expression during osteoblastic differentiation induction by zoledronic acid.